Exploring the Intersection of Software Engineering and Mobile Technology from 2010 to 2021: A Review of Recent Research - S M Nazmuz Sakib (Journal of Innovation Information Technology and Application (JINITA), 2023)
This paper presents a comprehensive review of recent research on the intersection of software engineering and mobile technology. The review method involves a systematic literature search and analysis of relevant research articles. The study identifies key trends and challenges in the field, including the need for better testing and debugging tools, and the emergence of new technologies such as mobile cloud computing. Innovative solutions are proposed to address these challenges. The research focuses on topics such as mobile application development, mobile databases, and mobile security. The paper provides a concise summary of the major findings and proposed solutions. The study concludes that the field of software engineering and mobile technology is rapidly evolving, and further research is needed to effectively address the challenges and keep pace with the dynamic nature of the field